Theoritical model of Responsiveness in Nursing Care: A Review - Sari Dewi Karuaniawathy; Nurfika Asmaningrum; Iis Rahmawati (Jurnal Ners, 2025)
Background : In nursing, responsiveness is a key component for improving service quality, patient satisfaction, and equity across healthcare systems. The purpose of this systematic review was to identify and analyze theoretical models and frameworks important to nursing. Methods: Literature was retrieved from major databases (Scopus, PubMed, ScienceDirect, and Scholar) through June 2024. This study highlights the importance of models or frameworks for addressing health or safety issues, whether based on theory, intervention, or model evaluation. Data were analyzed thematically to identify key dimensions and components of responsive models. Results: Each article identified highlighted diverse settings and populations. Thematic analysis revealed that multifaceted responsive models comprised sector-specific collaboration, equity, dignity, autonomy, effective communication, business practices, and patient-centered care. There was a positive relationship between the implementation of these models and patient outcomes and satisfaction, as well as improvements in service quality and performance. Key factors were the organizational environment, cultural adaptation, and student reluctance. Conclusion: Responsive nursing theory can be used to develop nursing practices and procedures that are more flexible, responsive, and sensitive to patient needs across healthcare systems.